Reciprocity of Sandwich Generations and the Bonding of Emotional Relationships in Family - Damayanti, Liony Alvina; Laksono, Arido; Purwanti, Tari (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
This study aims to analyze the phenomenon of reciprocity in the context of the sandwich generation and its impact on the emotional bonding among family members. The research was conducted by using a qualitative phenomenological approach, which allows researchers to gain an in-depth understanding of the experiences and perceptions of the sandwich generation actors. Four families with different social and cultural backgrounds were involved in this research, which was conducted in Pandean Lamper Village. The research data was obtained through in-depth interviews and observations, in which the sandwich generation actors shared their experiences in carrying out their dual role as providers. The results show that reciprocity plays a significant role in forming emotional bonds among members of the sandwich generation family. Two of the four families studied have balanced reciprocity. Meanwhile, the other two families experience an imbalance in reciprocity. In conclusion, this study confirms that balanced reciprocity in sandwich generation actors can help build strong bonds and improve overall family well-being. However, an imbalance of reciprocity can have a negative impact on emotional relationships within the family. Therefore, it is advisable to implement measures that support balanced reciprocity, such as open communication, fair division of responsibilities. Thus, the sandwich generation can create strong bonds and improve their overall quality of life.